2010
DOI: 10.1890/08-2168.1
|View full text |Cite
|
Sign up to set email alerts
|

Consumer return chronology alters recovery trajectory of stream ecosystem structure and function following drought

Abstract: Consumers are increasingly being recognized as important drivers of ecological succession, yet it is still hard to predict the nature and direction of consumer effects in nonequilibrium environments. We used stream consumer exclosures and large outdoor mesocosms to study the impact of macroconsumers (i.e., fish and crayfish) on recovery of intermittent prairie streams after drying. In the stream, macroconsumers altered system recovery trajectory by decreasing algal and macroinvertebrate biomass, primary produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 81 publications
3
26
0
Order By: Relevance
“…In general, nutrient influence intensified with time, whereas dace influence attenuated. A weakening dace effect is contrary to the observed strong effect of grazing minnows on algal biomass during baseflow conditions in some streams (Power et al 1988b, Gelwick andMatthews 1992), but is consistent with results reported by Murdock et al (2010), who found decreasing large-consumer effects during prairie stream recovery from drought. Murdock et al (2010) attributed this pattern to changing grazer communities and increasing macroinvertebrate grazing during succession.…”
Section: Time Dace and Nutrient Interactionssupporting
confidence: 88%
See 1 more Smart Citation
“…In general, nutrient influence intensified with time, whereas dace influence attenuated. A weakening dace effect is contrary to the observed strong effect of grazing minnows on algal biomass during baseflow conditions in some streams (Power et al 1988b, Gelwick andMatthews 1992), but is consistent with results reported by Murdock et al (2010), who found decreasing large-consumer effects during prairie stream recovery from drought. Murdock et al (2010) attributed this pattern to changing grazer communities and increasing macroinvertebrate grazing during succession.…”
Section: Time Dace and Nutrient Interactionssupporting
confidence: 88%
“…A weakening dace effect is contrary to the observed strong effect of grazing minnows on algal biomass during baseflow conditions in some streams (Power et al 1988b, Gelwick andMatthews 1992), but is consistent with results reported by Murdock et al (2010), who found decreasing large-consumer effects during prairie stream recovery from drought. Murdock et al (2010) attributed this pattern to changing grazer communities and increasing macroinvertebrate grazing during succession. Dace appeared to have little influence on periphyton recovery because their effect was greatest soon after flooding, and the change from weak dace control to strong nutrient control coincided with the start of exponential algal growth.…”
Section: Time Dace and Nutrient Interactionssupporting
confidence: 88%
“…Information comparing effects of stream consumers on ecosystem structure and function across biomes is limited. Grazing fishes can have strong effects on periphyton communities and nutrient cycling in desert (Grimm 1988) and grassland streams (Power et al 1985, Murdock et al 2010, Kohler et al 2011) that have relatively high rates of autochthonous production. The role of shrimp and crayfish in litter processing probably increases in forested tropical and temperate streams (Huryn andWallace 1987, Crowl et al 2001).…”
Section: How Ecological Responses Of Animals Change Across Biome Gradmentioning
confidence: 99%
“…3, 4) could have been due to changes in algal community composition. For instance, grazers may have selected against long filamentous algae, resulting in a different algal community (Murdock et al 2010;Power et al 1985). Additionally, pevious work has documented conflicting patterns of the effects of native grazers on GPP.…”
Section: Top-down and Bottom-up Effects Of Grazing Invadersmentioning
confidence: 99%